PENGARUH GAYA KEPEMIMPINAN DAN TALENT MANAGEMENT TERHADAP PENGEMBANGAN KARYAWAN PADA PT. MARSYAVIN JAYA KABUPATEN MERAUKE - Maria Kaok; Ria Mardiana Yusuf; Andi Ratna Sari Dewi (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
Human resources (HR) is the most important asset or capital for an organization or company. This study aims to determine the influence of Leadership Style and Talent Management Against Employee Development At PT. Marsyavin Jaya Merauke Regency. This research is a quantitative research where this research use survey method with path analysis technique to know influence between independent variable and dependent variable at PT. Marsyavin Jaya Merauke Regency. The results of this study found that leadership style has a positive effect on employee development, leadership style positively affects talent management, talent management has a positive effect on employee development. The talent management can mediate the influence of leadership style on the development of employees at PT. Marsyavin Jaya Merauke Regency.